Implementasi Metode Hybrid Learning Pada Mata Pelajaran Pendidikan Agama Islam Terhadap Peningkatan Akhlak Peserta Didik - Andi Fitriani Djollong; Sumadin Sumadin; Rosmiati Ramli; Makki Makki; Yenni Zulfahdar (Institute of Advanced Knowledge and Science, 2024)
This research aims to determine the morals of students and determine the influence of the Hybrid Learning method in Islamic religious education subjects on improving the morals of students at UPTD SMPN 4 Parepare. The research uses a qualitative approach, there are two data sources used, namely primary data sources and secondary data sources, the key research instrument is the researcher himself, the data collection techniques used are observation, interviews and documentation, the data analysis technique used is data reduction, presenting data, and drawing conclusions. The research results show that: Students' morals have decreased since post-pandemic learning. Implementation of the Hybrid Learning method in Islamic Religious Education Subjects to improve students' morals, namely the Hybrid Learning method can support the improvement of students' morals but on the other hand it can also hinder the improvement of students' morals if it is not implemented properly.